Effect of roasting on utilization of sunflower oil seeds in nursery pig diets - Fitzner, G.E.; Weeden, T.L.; Li, D.F.; Jones, D.B.; Hines, Robert H.; Goodband, Robert D.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred twelve weanling pigs were used to evaluate effects of diets containing 25% raw or low or high roasted sunflower seeds on performance. Pigs fed meal and pelleted diets containing sunflower seeds roasted to a roaster exit temperature of 264 of (low roast) were more efficient (F/G) than pigs fed raw sunflower seed diets in meal form. Pelleting raw, low roast, and high roast sunflower seed diets significantly improved F/G compared to raw sunflower seed and basal diets fed in meal form. These results indicate that meal diets containing 25% low roasted sunflower seeds or pelleted diets containing 25% raw or low roasted sunflower seeds can be fed to weaned pigs with no reduction in performance.
Keywords: Swine; Nursery pigs; Sunflower seeds; Roasting; Pelleting